Pemberian Suaka Diplomatik dalam Hukum Internasional: Dilema antara Aspek Kemanusiaan dan Tensi Hubungan Bilateral - Janardana Putri; I Made Budi Arsika (Undang: Jurnal Hukum, 2022)
Diplomatic asylum is a practice of granting international protection outside of state territory which is often carried out based on the extraterritorial theory and the principle of inviolability possessed by a state to carry out its diplomatic mission. In several cases, diplomatic asylum is sometimes regarded as reducing the sovereignty of a state which potentially leads to increasing bilateral tensions. However, humanity considerations as the reasons behind the granting of diplomatic asylum are appreciated by the international society. This article aims to discuss the existence of diplomatic asylum from the perspective of sovereignty and the legitimacy of diplomatic officials to grant diplomatic asylum. This article concludes that international law generally places state sovereignty and non-intervention as fundamental principles that must be respected. Both the Vienna Convention on Diplomatic Relations (1961) and the Vienna Convention on Consular Relations (1963) do not specifically regulate the issue of diplomatic asylum, therefore, its legal basis often refers to state practices. The granting of diplomatic asylum that is not based on humanity's interest may raise a controversy under international law. Instruments of international human rights law justify for diplomatic officials to grant asylum to people in need, especially in critical situations that threaten the safety of that person. Abstrak Suaka diplomatik merupakan praktik pemberian perlindungan internasional di luar wilayah teritorial suatu negara yang kerap dilakukan atas dasar eksistensi teori ekstrateritorial dan prinsip inviolabilitas yang dimiliki oleh suatu negara untuk melaksanakan misi diplomatiknya. Dalam beberapa kasus, pemberian suaka diplomatik terkadang dianggap mereduksi kedaulatan suatu negara sehingga berpotensi meningkatkan tensi hubungan bilateral. Hanya saja, dalil kepentingan kemanusiaan sebagai dasar pemberian suaka diplomatik justru diapresiasi oleh masyarakat internasional. Artikel ini bertujuan untuk membahas mengenai eksistensi suaka diplomatik yang ditinjau dari perspektif kedaulatan dan legitimasi pejabat diplomatik untuk memberikan suaka diplomatik. Artikel ini menyimpulkan bahwa hukum internasional pada umumnya menempatkan kedaulatan negara dan non-intervensi sebagai prinsip-prinsip penting yang harus dihormati. Baik Konvensi Wina mengenai Hubungan Diplomatik (1961) maupun Konvensi Wina mengenai Hubungan Konsuler (1963), tidaklah secara spesifik mengatur persoalan suaka diplomatik, oleh karenanya suaka diplomatik berkembang pada praktik negara-negara. Pemberian suaka diplomatik yang tidak didasarkan dengan kepentingan kemanusiaan dapat memunculkan kontroversi dalam hukum internasional. Instrumen hukum hak asasi manusia internasional memberikan justifikasi bagi pejabat diplomatik untuk memberikan suaka kepada orang yang membutuhkan, khususnya dalam situasi genting yang mengancam keselamatan orang tersebut.